Acute Lower Extremity Fracture Management in Chronic Spinal Cord Injury: 2022 Delphi Consensus Recommendations. Issue 4 (8th October 2022) - Carbone, L.D.; Ahn, J.; Adler, R.A.; Cervinka, T.; Craven, C.; Geerts, W.; Hsu, J.R.; Huang, D.; Karunakar, M.A.; Kiratli, B.J.; Krause, P.C.; Morse, L.R.; et al.
Abstract : Background: Our objective was to develop a clinical practice guideline (CPG) for the treatment of acute lower extremity fractures in persons with a chronic spinal cord injury (SCI). Methods: Information from a previous systematic review that addressed lower extremity fracture care in persons with an SCI as well as information from interviews of physical and occupational therapists, searches of the literature, and expert opinion were used to develop this CPG. The Grading of Recommendations, Assessment, Development and Evaluations (GRADE) system was used to determine the quality of evidence and the strength of the recommendations. An overall GRADE quality rating was applied to the evidence. Conclusions: Individuals with a chronic SCI who sustain an acute lower extremity fracture should be provided with education regarding the risks and benefits of operative and nonoperative management, and shared decision-making for acute fracture management should be used. Nonoperative management historically has been the default preference; however, with the advent of greater patient independence, improved surgical techniques, and advanced therapeutics and rehabilitation, increased use of surgical management should be considered. Physical therapists, kinesiotherapists, and/or occupational therapists should assess equipment needs, skills training, and caregiver assistance due to changes in mobility resulting from a lower extremity fracture. Therapists should be involved in fracture management as soon as possible following fracture identification. Pressure injuries, compartment syndrome, heterotopic ossification, nonunion, malunion, thromboembolism, pain, and autonomic dysreflexia are fracture-related complications that clinicians caring for patients who have an SCI and a lower extremity fracture may encounter. Strategies for their treatment are discussed. The underlying goal is to return the patient as closely as possible to their pre-fracture functional level with operative or nonoperative management.